Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena National Public Lecture Series by Tan Sri Dr Noorul Ainur Mohd Nur - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
Alhamdulillah, by the grace and blessings of Allah Ta’ala, we are able to meet here this afternoon, for another edition of UMP National Public Lecture Series.